1996
DOI: 10.1097/00005392-199609000-00064
|View full text |Cite
|
Sign up to set email alerts
|

Transitional Cell Carcinoma Involving the Prostate with a Proposed Staging Classification for Stromal Invasion

Abstract: Prostatic urethral or ductal transitional cell carcinoma does not alter survival determined by primary bladder stage alone and it should not be classified as P4a. Prostatic stromal involvement arising intraurethrally significantly decreases survival predicted by primary bladder stage alone. P1 bladder tumors with prostatic stromal invasion arising intraurethrally have a significantly higher survival rate than P4a tumors and they should be separately classified as P1str. Muscle invasive (P2/P3a) bladder tumors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
54
0
1

Year Published

1999
1999
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(57 citation statements)
references
References 14 publications
2
54
0
1
Order By: Relevance
“…Invasion of the prostate by urinary bladder urothelial carcinoma ( Figure 8D) may occur in three ways: (1) intra-urethral, (2) extravesical and (3) bladder neck invasion. [122][123][124] Spread of urothelial carcinoma through the urethra with subsequent invasion into prostatic stroma is not considered direct invasion of the prostate; rather, this situation is staged using the urethral cancer staging system for the urethral/prostatic tumour and a separate stage for the urinary bladder tumour ( Table 2). The extravesical and bladder neck pathways into the prostate occur less frequently than intra-urethral spread.…”
Section: P R O S T a T I C I N V A S I O Nmentioning
confidence: 99%
See 2 more Smart Citations
“…Invasion of the prostate by urinary bladder urothelial carcinoma ( Figure 8D) may occur in three ways: (1) intra-urethral, (2) extravesical and (3) bladder neck invasion. [122][123][124] Spread of urothelial carcinoma through the urethra with subsequent invasion into prostatic stroma is not considered direct invasion of the prostate; rather, this situation is staged using the urethral cancer staging system for the urethral/prostatic tumour and a separate stage for the urinary bladder tumour ( Table 2). The extravesical and bladder neck pathways into the prostate occur less frequently than intra-urethral spread.…”
Section: P R O S T a T I C I N V A S I O Nmentioning
confidence: 99%
“…The extravesical and bladder neck pathways into the prostate occur less frequently than intra-urethral spread. [123][124][125][126][127][128][129][130] The reported incidence of direct involvement of the prostate by urinary bladder cancer is somewhat variable, due probably to differences in patient populations and method of processing the cystoprostatectomy specimens, but it is not rare, occurring in 7-38% of male patients who underwent radical cystoprostatectomy. [123][124][125][126][127][128][129][130] The distinction between invasion of prostatic stroma by a urethral tumour (i.e.…”
Section: P R O S T a T I C I N V A S I O Nmentioning
confidence: 99%
See 1 more Smart Citation
“…This difference was highly significant (p<0.0001). Esrig et al [46]identified 143 (29.2%) out of 489 men that had prostatic involvement by transitional cell carcinoma in the cystectomy specimen and reported a 5–year overall survival rate of 74.3% for carcinoma in situ in the urethra of the prostate compared with 67% for tumor in prostatic ducts and 35.8% for stromal invasion of the prostate. Five–year overall survival was significantly higher for patients without stromal invasion compared to tumors with prostatic stromal invasion (p = 0.0001).…”
Section: Prostatic Involvement: Significance Of Invasion Depth and Prmentioning
confidence: 99%
“…A meticulous pathologic assessment of the cystoprostatectomy specimen is therefore recommended to describe the route of invasion and identify patients that are at high risk for local or systemic recurrence and may benefit from adjuvant treatment. The significant detection rate of prostatic involvement [45, 46, 47]should make us aware of the importance of carefully evaluating this entity in surgical specimens.…”
Section: Prostatic Involvement: Significance Of Invasion Depth and Prmentioning
confidence: 99%